2016
DOI: 10.1063/1.4937948
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of nitrogen injection at trans- and supercritical conditions

Abstract: Large-eddy simulations (LESs) of cryogenic nitrogen injection into a warm environment at supercritical pressure are performed and real-gas thermodynamics models and subgrid-scale (SGS) turbulence models are evaluated. The comparison of different SGS models — the Smagorinsky model, the Vreman model, and the adaptive local deconvolution method — shows that the representation of turbulence on the resolved scales has a notable effect on the location of jet break-up, whereas the particular modeling of unresolved sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…Non-ideal correction of sensible enthalpy and isobaric heat capacity are expressed in terms of departure functions derived from the particular EoS, whereas quantities for the hypothetical, ideal gas state are calculated using seven-coefficient NASA polynomials [33] (National Aeronautics and Space Administration). Note, as pointed out by [20] and others, that it is not feasible to include the volume-translation method of [32] in the caloric equation of state. Therefore, no c p values are shown for the PRC-EoS.…”
Section: Thermodynamic and Transport Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-ideal correction of sensible enthalpy and isobaric heat capacity are expressed in terms of departure functions derived from the particular EoS, whereas quantities for the hypothetical, ideal gas state are calculated using seven-coefficient NASA polynomials [33] (National Aeronautics and Space Administration). Note, as pointed out by [20] and others, that it is not feasible to include the volume-translation method of [32] in the caloric equation of state. Therefore, no c p values are shown for the PRC-EoS.…”
Section: Thermodynamic and Transport Modelsmentioning
confidence: 99%
“…Studies related to LES have been reported in [19,20]. Thereby, the subgrid scale (SGS) models applied have been developed for subcritical flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In single phase systems the calculation of the speed of sound and the isenthalpic compressibility is almost straightforward, although it implies the calculation of some partial derivatives, which can be solved analytically for the cubic EoS used in this investigation, see, e.g., Müller et al [16] for the PR-EoS. In multi-phase systems this is not true anymore and the evaluation gets way more complicated.…”
Section: Name Symbol Equationmentioning
confidence: 99%
“…4 c) and Eq. (16). In order to do a further evaluation of the numerical approach described above, we also show the different compressibilities (ψ s , ψ h and ψ T ) in Fig.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation